BELIEFS AND STEREOTYPES IN HUMAN AGING - Almeida, Maria de Lurdes Ferreira de (2014)
Introduction According to the phenomenological theories, each person has her own perceptions of reality and builds her own reality. There are many different realities, as much as indivi¬duals themselves. Objectives This study looks for an interpretative view, the most conceivable as possi¬ble, of beliefs and stereotypes of aging, based on the plurality of opinions, expressed by nurses as well as on their care practices. Methods Therefore, an exploratory research was made, using interviews and partici-pant's observation. The study base population, were provided by nurses of Medicine and Neurology internment units of a Central Hospital. Results During the interviews, the nurses' concern to help old people was extremely vivid; on one hand, living with the physical limitations inherent to the aging and on the other hand, developing strategies to face loneliness and isolation very frequent at this stage of develop¬ment. By analysing the notes taken from observation, we must point out the effort put on the life maintenance of care, more connected with physical care. Conclusions Nurses keep stereotypes concerning old people, but what came up especially from the analysis of the collected information are the beliefs: Being old is being dependent; aging implies lack of capacities; the majority of old people suffer from loneliness; sick old people are rejected by the family.